2019
DOI: 10.3390/rs11020125
|View full text |Cite
|
Sign up to set email alerts
|

Soil Moisture Monitoring Using Remote Sensing Data and a Stepwise-Cluster Prediction Model: The Case of Upper Blue Nile Basin, Ethiopia

Abstract: In this study, a residual soil moisture prediction model was developed using the stepwise cluster analysis (SCA) and model prediction approach in the Upper Blue Nile basin. The SCA has the advantage of capturing the nonlinear relationships between remote sensing variables and volumetric soil moisture. The principle of SCA is to generate a set of prediction cluster trees based on a series of cutting and merging process according to a given statistical criterion. The proposed model incorporates the combinations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 71 publications
(124 reference statements)
4
10
0
Order By: Relevance
“…We can now say with high confidence that: (1) VV polarization is more sensitive than VH polarization for soil moisture retrieval; similar results have been found by [19][20][21][22][23]. (2) The combination of VV and VH polarization has resulted in improvement in the prediction of soil moisture from Sentinel-1 images, our result agree with [24][25][26]. (3) The best inputs to the CNN to retrieve soil moisture from Sentinel-1 images are Sigma0_VH and Sigma0_VV, or Gamma0_VH and Gamma0_VV, or Beta0_VH and Beta0_VV.…”
Section: Comparison Between Cnn Architecture (𝐶 𝐼𝐼 ) and Cnn Architecture (𝐶 𝐼𝐼𝐼 )supporting
confidence: 88%
See 1 more Smart Citation
“…We can now say with high confidence that: (1) VV polarization is more sensitive than VH polarization for soil moisture retrieval; similar results have been found by [19][20][21][22][23]. (2) The combination of VV and VH polarization has resulted in improvement in the prediction of soil moisture from Sentinel-1 images, our result agree with [24][25][26]. (3) The best inputs to the CNN to retrieve soil moisture from Sentinel-1 images are Sigma0_VH and Sigma0_VV, or Gamma0_VH and Gamma0_VV, or Beta0_VH and Beta0_VV.…”
Section: Comparison Between Cnn Architecture (𝐶 𝐼𝐼 ) and Cnn Architecture (𝐶 𝐼𝐼𝐼 )supporting
confidence: 88%
“…VV polarization was more sensitive for soil moisture retrieval from Sentinel-1 data as compared to VH polarization [21][22][23]. Several studies have indicated that the accuracy of the soil moisture estimates improved when using both VV and VH polarization, instead of only VV or VH polarization [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, SCA was used to establish the statistical relationships between precipitation and geographical factors (latitude, longitude, elevation and slope). Based on these relationships, the research region could be divided into different sub‐regions to analyse the regional heterogeneity better (Ayehu, Tadesse, Gessesse, & Yigrem, 2019; Wang, Huang, Zhao, & Guo, 2015). The principle of SCA is to divide samples into a set of clusters with significant differences based on a series of cutting and merging processes according to a given statistical criterion.…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, many studies of soil water content (SWC) variability at a multitude of different spatio‐temporal scales have been conducted. For example, studies of only 20 m apart found profound differences at a local scale (Oerter & Bowen, 2019; Romano, 2014); surface SWC showed a greater effect on immediate plant responses at the field scale (Siegfried, Longchamps, & Khosla, 2019); spatial variability and temporal stability of soil water storage increased over depth at a watershed scale (Fu et al, 2018); higher SWC responses were linked to higher elevation at a regional‐scale (Ayehu, Tadesse, Gessesse, & Yigrem, 2019) and SWC trends were even noted in a global scale (Piles, Ballabrera‐Poy, & Munoz‐Sabater, 2019). Due to the variability and complexity of SWC, conventional in‐situ point‐scale measurements are not practicable for regional‐scale SWC assessment (Singh, Panda, & Mohanty, 2019).…”
Section: Introductionmentioning
confidence: 99%